The Effects of Infant Massage Therapy on Preterm Neonatal Outcomes: A Clinical Trial - Jiranun Weerakul; Yasinee Apiraknapanon; Mathayan Sanjaiban; Suneera Intasen; Supattra Tipsuwan; Mattana Bhumipraphat (International Journal of Pediatrics)
Conclusion: Infant massage therapy significantly enhances weight gain and reduces the time to achieve full feeding in VLBW preterm infants. Moderate-pressure massage is recommended for stable VLBW infants in neonatal intensive care units (NICUs).